Foam fractionation : principles and process design - Stevenson, Paul, 1973- (Taylor & Francis, 2014)
"Foam fractionation is a process in which proteins and other amphipathic species can be removed from solution by causing them to adsorb to the surface of bubbles, which are removed in the form of foam from the top of the column. This book describes the physics that underpin the process, much of which has been recently developed by the authors. It also discusses design factors in foam fractionation and describes process intensification strategies. Case studies include an example of the production of the food preservative Nisin. The book will be of interest to academics and practicing chemical engineers in the field of biotechnology"--